Evaluasi Usability Dengan Pendekatan System Usability Scale (SUS) Pada Aplikasi TMHub - Apriyanthi, Ni Putu Eka; Mentayani, Ni Putu Anik; Gunawan, I Made Agus Oka; Indrawan, Gede (Institut Bakti Nusantara, 2024)
The utilization of an easy and efficient application not only enhances user productivity but also contributes to increased satisfaction and retention. TMHub, a digital platform provided by Carnival, serves to deliver information and support to their team members. TMHub incorporates essential features such as Assignment Information, Required Documents, Enhanced Flights, Hotel, and Meet Greet Information. The research involves 35 student participants who use the TMHub application, aiming to investigate user perceptions and experiences through the analysis of data using the System Usability Scale (SUS) methodology. The study commences with the design of a SUS questionnaire comprising 10 questions to measure user perceptions and experiences regarding the TMHub application. The questionnaire covers aspects such as user-friendliness, clarity of information, and user satisfaction. Subsequently, respondents are requested to fill out the questionnaire after using the TMHub application. It is anticipated that Carnival can identify specific measures to enhance the quality of services offered to their team members through the findings of this research. Additionally, the study holds the potential to significantly contribute to the broader research on mobile application usability. The questionnaire results indicate an average score of 78 from respondent feedback. Among the questions posed to respondents, their responses reveal both positive and negative aspects related to the use of the TMHub application.